RETRACTED: Influence of copolymers of acrylamide and acrylic acid on the structure and water strength of soil - Abdikamalova Aziza; Kuldasheva Shakhnoza; Eshmetov Izzat; Boymirzaev Azamat; Kholnazarov Bakhodir (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001